Lumbrineridae (Polychaeta) from the Portuguese continental shelf (NE Atlantic) with the description of four new species - Martins, Roberto; Carrera-Parra, Luis F.; Quintino, Victor; Rodrigues, Ana Maria (Zootaxa, 2012)
The present study reports four new species of the Family Lumbrineridae Schmarda, 1861, three in the genus Lumbrinerisde Blainville, 1828 and one in the genus Gallardoneris Carrera-Parra, 2006. The new species were found on the Portu-guese continental shelf at water depths ranging from 11 to 190 m. Gallardoneris iberica sp. nov. is the first record of thisgenus in the Atlantic Ocean and can be distinguished from the other two known Gallardoneris species by the distributionof the composite and the simple multidentate hooded hooks and the shape of the parapodial lobes. Lumbrineris luciliaesp. nov. has an arcuate, unidentate MIII and MIV unidentate with well-developed plate, digitiform wide basallypostchaetal lobes in anterior parapodia, composite multidentate hooded hooks with short blade. Furthermore, L. luciliaesp. nov. has simple multidentate hooded hooks of two sizes, preacicular hook twice as big as postacicular hook, and dis-tally curved aciculae in median and posterior parapodia. Both Lumbrineris lusitanica sp. nov. and Lumbrineris pinastersp. nov. are characterized by having MIII unidentate followed by a knob. However, L. lusitanica sp. nov. has digitiformwide basally postchaetal lobes in the anterior parapodia, composite multidentate hooded hooks with short blade and simplemultidentate hooded hooks with short hood; while L. pinaster sp. nov. has auricular postchaetal lobes in the anteriorparapodia, composite multidentate hooded hooks with long blade, and simple multidentate hooded hooks with short andlong hood. A multivariate analysis was performed upon morphological characteristics and validates the separation of the four new species. A taxonomic key to lumbrinerid species from Iberian waters is included.